PERSEPSI ORANG TUA TENTANG PELAKSANAAN PEMBELAJARAN DI PAUD AN-NISA KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Nova, Delvia; Indarto, Wusono; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the perception of parents about early childhood learning implementation An- Nisa Tanah Putih Rokan Hilir. This research is descriptive . population and sample in this study are all parents in early childhood An- Nisa totaling 33 people . The data used in this study are primary data , the instrument used was a questionnaire ( questionnaire ) , while the technique of data analysis in this study using a percentage formula . The results showed that from 3495 the overall indicator score obtained by the percentage of 62.30 % are in the good category , while for each indicator , the indicators obtained cognitive percentage of 60.66 % is in the category enough , affective indicators obtained a percentage of 66.79 % are in the good category and indicator connative obtained a percentage of 60.20 % in the category enough.Keywords: Perception, Learning Implementation..